Integrasi Pendidikan Lingkungan dalam Bahan Ajar di Sekolah Untuk Membentuk Kesadaran Berkelanjutan - Srihartini, Yusi; Maryam, Siti; Trisnawati, Nia (Ikatan Dai Indonesia, 2025)
The global environmental crisis not only affects human well-being but also threatens the sustainability and continuity of nature itself. In response to this crisis, various efforts have been made; however, they remain sporadic and reactive rather than preventive, resulting in ongoing environmental degradation. Therefore, environmental awareness must be cultivated as early as possible, including through the integration of environmental education into the development of teaching materials in schools. Education can serve as a medium to enhance awareness, knowledge, attitudes, and even personality or behavior, including awareness of the environment and its sustainability. This study aims to examine the integration of environmental education into the development of teaching materials implemented in schools and the role of these integrated teaching materials in fostering sustainable awareness among students, which impacts their attitudes and interactions with the environment. The results of the study indicate that the integration of environmental education into teaching materials can be applied across various subjects. These teaching materials are then developed using engaging and contextual learning strategies, such as Problem-Based Learning, Project-Based Learning, and the utilization of technology in teaching. This development enhances students' environmental competence in cognitive, affective, and psychomotor aspects.